FINANCIAL REPORTING FRAUD: AUDIT COMMITTEE AS MODERATION - Mohamad Zulman Hakim; Epekele Wisdom; Dirvi Surya Abbas; Alvina Anggraini; Gadis Ayu Rizky Darmala; Elsa Audia Utami (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to investigate the influence of the audit committee in moderating the association between financial targets, financial stability, changes in directors, ineffective supervision, optimal conditions of the company, changes in auditors, the CEO's photograph, government projects, political connections, and managerial ownership on financial statement fraud. When examining instances of financial statement fraud, it is important to take into account the involvement of the audit committee in addition to other variables. The Beneish M-Score Model is used to quantify financial statement fraud. The study focuses on analyzing a sample of 49 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) between 2020 - 2021. The analysis employs panel data regression analysis with 98 units, utilizing the EViews 13 analytical tool to test the hypothesis. The findings of this study indicate that a company's financial target significantly impacts the likelihood of financial statement fraud. Factors such as financial stability, changes in directors, monitoring, the company's ideal condition, changes in auditors, CEO photographs, government projects, political connections, and managerial ownership do not affect the likelihood of financial statement fraud. The presence of an audit committee has a moderating effect on the occurrence of financial statement fraud as each independent variable becomes less influential.